Is it possible to perform molecular hybridization between acetaminophen and nitric oxide donor molecule? - João Gabriel Gouvêa-Silva; Leonardo Ribeiro Bernardo; Ygor Jessé Ramos; Antônio José Calixto de Souza (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2021)
Paracetamol (Acetaminophen) belongs to the class of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), having an analgesic, antipyretic and mild anti-inflammatory action due to a weak inhibitory action on cyclooxygenase isoenzymes, COX-1 and COX-2. These isoenzymes are responsible for the synthesis of prostanoids that have several physiological effects, such as: vasodilation; increased renal blood flow; stimulation of gastric protective mucus production; inhibition of gastric acid secretion responsible for reducing acidity in gastric tissue, among other effects. Despite its beneficial effects, the excessive use of NSAIDs is related to several adverse effects, which can alter the homeostasis of the cardiovascular, renal and gastric system [1].